Pakistan’s Struggle against Extremist Onslaught, Assimilating Women in Pakistan’s Counter-Extremism Efforts; A Critical Appraisal - Dr. Umbreen Javaid (Journal of Political Studies, 2018)
Radicalization and wide spread extremist ideologies culminating in organized acts of terrorism have become a great challenge for the contemporary modern world. The threat becomes more severe in the context of developing and underdeveloped societies where state infrastructure is in nascent stages and hence, cannot face such complex and daunting threats. The penetration and expansion of the radical ideas by the use of modern tools of information technology and innovative means of communication facilitate the radical outfits which have serious ramifications for all sections of society but youth being receptive to emotional and adventurous ideologies and slogans of change are most vulnerable. In case of Pakistan, where terrorism in the name of religion has become the most terrifying phenomena incurring heavy losses on the country’s weak economy, the youth of Pakistan need to be educated, enlightened and equipped intellectually and conceptually against the extremist milieu. The task is gigantic and involves comprehensive de-radicalization and counters radicalization programs and in case of Pakistan’s meager resources allocated for education the task is a far cry. In this connection the role of women needs to be focused and utilized given the Pakistan’s specific socio-cultural context wherein the role of mother is like that of a nucleus. The present study aims to focus on the importance of the role of women in inculcating counter radicalization attitudes and ideas in the young generations and will explore possible suggestions to enhance role of women in CVEs efforts at various levels in the society.